Structure and function of the zona pellucida: current state of knowledge - Abdul Rahman, Suzanah; Ahmad, Nur Amalina (2017)
The mammalian zona pellucida is an extracellular matrix that surrounds the oocytes and embryos up until the stage of hatching of the blastocyst. It functions to facilitate sperm-oocyte binding by stimulating acrosome reaction and to protect the embryo through its journey in the fallopian tube. Prevention of polyspermy is also attributed to the hardening of the zona pellucida. In human assisted reproductive technologies (ART), it is crucial to identify objective evidence of the quality indicators of gametes and eventually the developing embryo that would be viable for transfer. Each developmental step of the embryo and the modifications to the structure and function of the zona pellucida have been examined by means of microscopy, chemical and immunodetection, imaging and computer modelling. Investigations on the zona pellucida range from measurements of the varying thickness of the structure including the production of the glycoprotein layers by the granulosa cells and their specific roles during fertilization, physicochemical alterations during the hardening of the structure and ovastacin activity. Molecular basis of oocyte maturity and fertilization capacity have also been shown to relate to the mRNA expression of the genes in the glycoprotein layers of the human oocyte and the surrounding cumulus cells. The characteristics of the zona pellucida including the birefringence of the inner zona layer have since become indicators of embryonic development. Non-invasive visualization of inaccessible structures in the zona pellucida that is applicable in the laboratory to aid the classification of embryos could well serve as an important prognostic tool in ART.